Tips for First Time Teaching Assistants: A Personal Narrative - Maya El Shareef (Networks: An Online Journal for Teacher Research, 2006)
The TA experience may be something new to many graduate students. Sharing the experiences of one TA can assist others who are new to this responsibility. This paper provides broad guidelines for TAs based on my personal experience of being a teaching assistant for three different courses over one academic year. It provides TAs with tips on important topics such as: their relationships with course instructors, their relationships with students, grading of student papers, session evaluations, teaching methodology, as well as the proper ways of introducing change, particularly in the use of technology.